Counseling and counseling services status in Ethiopia - Disassa, Getachew Abeshu (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2020)
The underlying point of reference in the study was obtaining relevant information from modern and professional counselors in the country in view of the societal understanding and interest of using the counseling services in their lifetime. The counseling organizations involved in the study were chosen representing practices of modern counseling structure in the study that has based on certain relevance they could have for the intended lessons. Qualitative study method was conducted employing framework data analysis technique. The tools used to gather information were interview, observation and focus group discussions with key informants of the institutions. The study result identified that even though counseling and counseling service quality is at promising status, much is expected from concerned government and non-government organizations in boosting the purpose and functions of counseling in maintaining adolescents’ holistic development in and out of school. Consequently, counseling as a tradition among Ethiopian community, specifically the Oromo, become practical to maintain peaceful mental and social serenity of the community with further consideration to progress.